2017
DOI: 10.20944/preprints201711.0115.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Sales Behavior Analysis and Precise Marketing Recommendations of FMCG Retails Based on Geography Methods

Abstract: With the rapidly increasing of people’s purchasing power, the fast moving consumer goods (FMCG) industry is supposed to grow dramatically. In order to gain more market access and profile, it is important for the FMCG manufacturers and retailers to find the preferences and provincial characteristics of consumers, to develop more suitable goods distribution strategy. Based on retails marketing data with geographic characteristics, this paper proposes a new combination of geography methods to solve the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Furthermore, the role of data-driven insights in shaping marketing strategies cannot be overstated. Wang et al (2017) underscored the value of using geographic methods to analyze sales behavior and develop precise marketing recommendations for FMCG retails. By harnessing the power of data analytics, FMCG brands can gain a deeper understanding of market trends, consumer preferences, and competitive landscapes.…”
Section: Suggestions For Future Crisis Marketing Preparednessmentioning
confidence: 99%
“…Furthermore, the role of data-driven insights in shaping marketing strategies cannot be overstated. Wang et al (2017) underscored the value of using geographic methods to analyze sales behavior and develop precise marketing recommendations for FMCG retails. By harnessing the power of data analytics, FMCG brands can gain a deeper understanding of market trends, consumer preferences, and competitive landscapes.…”
Section: Suggestions For Future Crisis Marketing Preparednessmentioning
confidence: 99%
“…For example, [22] concluded that integrating K-Means clustering and the spatial Getis-Ord G * i statistic resulted in a superior technique for identifying clusters of orchards. In another study, [23] employed multiple K-Means clustering and Moran's I spatial autocorrelation method to find the preferences and provincial characteristics of consumers in the retail industry. In [24] Scrucca implemented K-Means clustering and measures of spatial autocorrelation to incorporate the spatial structure of the labor market data in Umbria, Italy.…”
Section: Literature Reviewmentioning
confidence: 99%